Analisis Permintaan Bahan Pokok Beras Pada Saat Pandemi Covid-19 di Indonesia - Dian Isnawati; Wahyu Lestari; Alvindo Ichwan Jati (Inspirasi Nusantara, 2022)
This study aims to analyze the average percentage of consumption per capita per week, how much rice is produced in Indonesia, how much is the data on production, harvested area and productivity of rice, as well as policies implemented by the government. This study uses secondary data from BPS that has been processed, this study uses quantitative approach analysis. The results of the study are based on BPS data in September 2019, that the average consumption of rice is 87.03%. This figure is close to 100%, which means that the consumption of rice demand is very high. This commodity still uses rice as its main ingredient. Second, the current state of the COVID-19 pandemic does not cause a significant increase or decrease in consumption, but the community continues to strive to meet these needs, regardless of the conditions and methods. Furthermore, during the COVID-19 pandemic, total rice production decreased, but in early 2021 it had started to increase again. Production of rice stocks has spread everywhere in Indonesia which is equal to the sum of the rice harvested area and the total resulting from the productivity of the rice. Lastly, the government's policy during the COVID-19 pandemic was to tackle the existence of a rice monopoly or rice hoarding.